Effective Participation? Child and Youth Welfare Services between Enhancing Capabilities, Forced Inclusion and Demands for Evidence and Effectiveness - Stefanie Albus; Bettina Ritter (Social Work & Society, 2019)
In times of New Public Management, Evidence-based Policy and Practice and new concepts of funding like Social Impact Bonds there is an increased and vehement interest in the impact of Social Work practice. In so far the question of aims and processes in Social Work is no longer only a matter of professional evaluation of socialpaedagogical practice but raised in political debates. However which evaluative ends should be chosen and which means can meet these ends? To whom it is useful and desirable? Especially in debates about child and youth welfare service and service for people with disabilities there is a new focus on participation ("Teilhabe") as one central criteria of effectiveness. In this paper the emancipatory and repressive implications of different understandings of participation will be examined. This cursory insight will be referred to theoretical approaches to the modern welfare state and social services to elicit the progressive potentials of Social Work.